PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN RME UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA TAHUN AJARAN 2019/2020 - Muhajir Duka; St. Muthmainnah Yusuf; Uke Ralmugiz (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
The porpose of thesis this reseach to improve the mathematical communication skills of student of class VIII junior higth school Muhammadiyah Kupang towards learning mathematics using the RME approach, March 2020. There are two data colaction teach techniques used in this study, namely test and non-test. This type of reseach used in this reseach is development reseach. The design in this study is the ADDIE (Analysis, Design, development, Implementation, Evaluation). The analysis technique used in this study is quantitative data analysis consiss of analysis validity, practicality and effectiviness. The result of this study incate that the validiity of the develpment of learning tools with the RME apprroach in the RPP is 98.21 and hhe LKS 93.45 categorized as very good. Is it said to be practical because it is based on observations that the learning the device with the the RME approach on the flat side room building material in class VIIIB was carried out well during the tria. It is said to be effective because it has met the catagory that is the reference for the results of the mathematical communitation tes in the complelete catagori. So it can concluded that the developed learning device is declared valid, practical and effective in learning mathematics so that it can improve student learning outcomes.